Papel do exercício físico aeróbio na modulação das disfunções neuroimunes: avaliações em modelo experimental de sepse e de síndrome metabólica - Ferreira, Guilherme Lemos Shimojo (2018)
The integrations of neural networks represent efficient mechanisms selected by evolution to coordinate physiological homeostasis. It is interesting to note that correlations were demonstrated between cardiovascular and metabolic dysfunctions with autonomic and inflammatory (neuroimmune) disorders. Physical exercise is an important approach to prevent dysfunctions associated with diseases. Thus, recent studies focus on mechanisms induced by exercise to control these dysfunctions. In this thesis, we evaluated the effects of acute or chronic aerobic exercise on neuroimmune dysfunctions induced by experimental models of sepsis or metabolic syndrome. To reach these objectives, we divided the present study into 2 studies. In the first study, we reported that an exercise session of moderate intensity attenuates inflammation and organic dysfunction through dopamine induction mediated by activation of the vagus nerve. Exercise increased serum dopamine levels and adrenalectomy hindered the exercise potential of inducing dopamine and attenuating TNF. The D1 dopaminergic agonist, fenoldopam, inhibited TNF production in splenocytes. On the other hand, the D1-antagonist, butaclamol, prevented control of TNF exercise. In the second study, the consumption of fructose induced impairment in the variability of pulse interval (VAR-IP) since the 7-day protocol. In addition, there was an increased sympathovagal balance at 15, 30 and 60 days of protocol compared to the other groups. TF prevented the observed injury in the VAR-IP with 7 days of protocol, and improved the sympatho-vagal balance (FT vs. F). We observed a reduction in redox balance, protein oxidation as well as reduction of superoxide dismutase enzyme activity in the F groups at 7, 15, 30 and 60 days of protocol in relation to groups C. In addition, the consumption of fructose induced an increase of lipid oxidation at 30 and 60 days (F vs. FT). TF was effective in preventing these losses induced by chronic fructose consumption. In addition, TF prevented the increase of inflammatory mediators (TNF alpha and IL-6) and NF-Kappaβ observed in the fructose groups from 15-30 days of protocol, as well as increased levels of IL- inflammatory). Together our findings reinforce the role of the autonomic nervous system in the genesis of cardiometabolic dysfunctions and show an important role of aerobic physical training in the prevention of these alterations. In conclusion, our results show that neuroimmune dysfunctions occur early in experimental models of sepsis or metabolic syndrome and that aerobic physical exercise of moderate intensity is effective in preventing / attenuating such alterations, impacting on prevention of clinically detectable cardiometabolic alterations in these conditions. However, future studies are needed to determine how different types of exercise regulate different neural networks and their contribution to the cardiovascular, metabolic and immunological benefits induced by exercise. These studies may allow the design of new approaches for the treatment of neuroimmune and cardiometabolic diseases